Bipolar Type I Disorder in Children - Syaiful Fadilah; Fatimah Haniman (HM Publisher, 2020)
Bipolar disorder in children and adolescents is a clinical disorder that causes publicmental health problems that need attention. In the last decade, bipolar disorder inchildren and adolescents has become a trendy field, both in the clinical area and inresearch, especially in terms of diagnosis, which is still controversial. The controversythat remains is whether it is possible to diagnose bipolar disorder in prepubertalchildren. Based on the DSM-IV-TR diagnostic criteria, the prevalence of the bipolardisorder in children scarce rare. Epidemiological studies report the lifetimeprevalence of bipolar I and II disorders in late adolescence is about 1 per cent. Variousstudies in a large population have shown a prevalence rate of 0.1% -2%. The onsetof bipolar disorder in children and adolescents is often accompanied by a more severedisease course, compared to bipolar disorder with onset in adulthood. This casereport presents a case of bipolar 1 in children accompanied by comprehensivemanagement.